Fostering energy transition in Africa: Financial systems, inclusive growth, corruption control and ICT as catalysts - Louis David Junior Annor; Thomas Kyei-Mensah; John Agyekum Addae; Margarita Robaina; Elisabete Vieira (Sustainable Environment)
This study examines the dynamic interplay between financial markets and institutions access and depth, corruption control, inclusive growth, and ICT diffusion in promoting renewable energy consumption and clean cooking fuel technologies. Data were collected from World Development Indicators, the United Nations Development Programme, World Governance Indicators and the International Monetary Fund for 15 West African economies from 1996 to 2021. Using feasible generalized least squares (FGLS) as the primary estimator and panel-corrected standard errors (PCSE) for the sensitivity test, this study found that access and depth in financial markets drive up the use of renewable energy. Similarly, the depth and accessibility of financial institutions enhance this beneficial impact. Interestingly, we discovered that corruption control had two effects on renewable energy: negative direct effects on renewable energy consumption and positive moderating effects on the link between financial systems and green energy use. Inclusive growth negatively impacts renewable energy, but corruption control mitigates this negative effect. Inclusive growth, directly and indirectly, improves clean cooking fuel technology via corruption control. This study provides crucial insights for policymakers to address governance challenges, optimize financial market structures, and harness inclusive growth to augment renewable energy and clean cooking fuel technologies in West Africa.